Problems in the specialized music Lexicon: equivocities, multivocities and contradictions (2009)
It’s axiomatic that the main communication tools among the members of an academic community are, namely, the general written and spoken language used in a rigorous manner, it’s semantic specific scientific portion and it’s own symbolic system, when applic